A Comparative Investigation of Mechanical Properties of TiB2/Cr Multilayer Film by Indentation - Simeng Chen; Zhengtao Wu; Qimin Wang (Magnetochemistry, 2022)
Alternating TiB2-dcMS and Cr-HiPIMS layers are used to fabricate TiB2/Cr multilayer films. Introducing a 5-nm-thick Cr interlayer deposited under a substrate bias of −60 V produces slight increases in both film hardness and elastic modulus. The TEM observation indicates that the Cr grains favor epitaxial growth on the TiB2 interlayer, forming a coherent TiB2/Cr interface. This improves hardness. Mechanic measurement by using AFM illustrates that the coherent interface increases the elastic modulus of the Cr up to ~280 GPa, which is significantly higher than bulk material.